Exploring the mediating role of beauty influencer effectiveness on skincare products: Does credibility still influence purchase intention? - Desak Made Febri Purnama Sari; Made Ayu Sintya Nandini; Ni Made Sumarningsih; Ida Nyoman Basmantra (Review of Management, Accounting, and Business Studies, 2024)
The study explored the impact of beauty influencer credibility on purchase intention, focusing on how influencer effectiveness mediated this relationship. With the rise of social media platforms like Instagram and YouTube, beauty influencers have become key players in shaping consumer behavior, particularly in the competitive beauty industry where local brands like Somethinc compete with global brands. The research analyzed responses from 100 female teenagers aged 15-24 in Bali using Structural Equation Modeling (SEM) and Partial Least Squares (PLS) analysis. The results showed that beauty influencer credibility had a direct and positive effect on influencer effectiveness, with trust and expertise being critical factors. Influencer effectiveness significantly increased purchase intention, as consumers were more likely to make purchasing decisions when influencers communicated persuasively. Credibility also directly influenced purchase intention, but its effect was strengthened when mediated by influencer effectiveness. The findings highlighted that credibility alone was not sufficient; influencers needed to effectively engage their audience to maximize their impact. The study provided valuable insights for beauty brands, suggesting that selecting credible and effective influencers is crucial for successful digital marketing. It also opened avenues for future research into additional factors such as brand loyalty and price, and the potential for cross-cultural and longitudinal studies.